2019
DOI: 10.1371/journal.pone.0209989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of negative valence on assessment of self-relevance in female patients with borderline personality disorder

Abstract: BackgroundA disturbed self-image is central to the characteristic symptoms of borderline personality disorder (BPD). Evaluations of self-relevance (SR) are highly important in cognitive and emotional processing of information and adaptive behavior.MethodIn the current study, we used affective statements to investigate if SR is altered in patients with higher scores on Borderline Symptom List (BSL-95). Forthyfemale adults with BPD and 20 healthy participants assessed a set of stimuli consisting of sentences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Reduced functional connectivity between the DMN and occipital areas may be associated with an inflexible integration of sensory stimuli into self-referential processing in patients with BPD ( Wolf et al, 2011 ). A disturbed SR for negative statements in BPD has been indicated in previous literature ( Sarkheil et al, 2019 ). Our finding about reduced functional connectivity between the PCC and the occipital cortex for SR ratings of negative sentences provide additional evidence about SR is affected by negative contents in patients with BPD.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Reduced functional connectivity between the DMN and occipital areas may be associated with an inflexible integration of sensory stimuli into self-referential processing in patients with BPD ( Wolf et al, 2011 ). A disturbed SR for negative statements in BPD has been indicated in previous literature ( Sarkheil et al, 2019 ). Our finding about reduced functional connectivity between the PCC and the occipital cortex for SR ratings of negative sentences provide additional evidence about SR is affected by negative contents in patients with BPD.…”
Section: Discussionmentioning
confidence: 56%
“…In a previous study, we demonstrated a higher SR for negative sentences in female patients with BPD compared to healthy controls (HC). We also uncovered a positive correlation between the SR for negative sentences and the severity of BPD symptoms ( Sarkheil et al, 2019 ). Apart from this, most investigations of self-related processing in BPD have focused largely on the evaluation of self-esteem, revealing low ( Bungert et al, 2015 , Lynum et al, 2008 ) or unstable ( Hochschild Tolpin et al, 2004 ) self-esteem in this group of patients.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there were no differences in the Shame-IAT between healthy women and female patients with social phobia as compared to women with BPD in another study (Rüsch et al, 2007). Because a general negative evaluation bias for self-referential and self-relevant information is important in BPD and increases with its severity (Sarkheil et al, 2019; Winter et al, 2017), it may well be that our findings reflect a general association of BPD with any negative emotion or trait. This is particularly true as we included in-patients with BPD suffering from severe BPD pathology, for example, compared to BPD outpatients.…”
Section: Discussionmentioning
confidence: 79%